Augmented Reality "Smart Glasses" in the Workplace: Industry Perspectives and Challenges for Worker Safety and Health. Issue 4 (1st October 2016) - Kim, Sunwook; Nussbaum, Maury A.; Gabbard, Joseph L.
OCCUPATIONAL APPLICATIONS: Given advances in augmented reality head-worn display (AR HWD) technologies, "smart glasses" may become an everyday workplace tool in the foreseeable future, allowing workers to perform tasks hands-free while viewing real-time, task-relevant information within their visual field of view. Interviews with experts in several industries (e.g., chemical, medical, manufacturing, distribution) supported such future opportunities for AR HWD development, and underlined important practical concerns that should be overcome to bring smart glasses into mainstream, effective industrial use. Particularly, almost all interviewees believed that poorly designed interfaces for smart glasses may distract workers, yet saw potential in using well-designed AR HWD technology to improve workplace safety and health. This and earlier studies suggest that smart glasses can have important implications for human/task performance as well as workplace safety and health. Future research directions are discussed to promote and accelerate the safe adoption and implementation of AR HWD technologies in the workplace.